2021
DOI: 10.3390/math9050538
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanofluid Flow over a Permeable Non-Isothermal Shrinking Surface

Abstract: In this paper, we examine the influence of hybrid nanoparticles on flow and heat transfer over a permeable non-isothermal shrinking surface and we also consider the radiation and the magnetohydrodynamic (MHD) effects. A hybrid nanofluid consists of copper (Cu) and alumina (Al2O3) nanoparticles which are added into water to form Cu-Al2O3/water. The similarity equations are obtained using a similarity transformation and numerical results are obtained via bvp4c in MATLAB. The results show that dual solutions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 59 publications
(80 reference statements)
3
23
0
Order By: Relevance
“…In the last few years, various computational techniques have been utilized for various applications in the engineering research area [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In this study, ANN has been implemented for flow pattern identification and volume ratio prediction.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…In the last few years, various computational techniques have been utilized for various applications in the engineering research area [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In this study, ANN has been implemented for flow pattern identification and volume ratio prediction.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Note that l < 0 and l > 0 signify the shrinking and stretching sheets, respectively, while l = 0 is for the static sheet. Furthermore, the thermophysical properties are obtained from Oztop and Abu-Nada (2008), Takabi and Salehi (2014); and Waini et al (2021). Besides, the subscripts f and hnf are for the base fluid and the hybrid nanofluid, respectively.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Furthermore, Takabi and Salehi (2014) developed a new thermophysical model for hybrid nanofluid. Moreover, the magnetohydrodynamic (MHD) effects on the hybrid nanofluid flow have been studied by several authors (Aly and Pop, 2019; Faizal et al , 2020; Jamaludin et al , 2020; Khan et al , 2020; Waini et al , 2020a, 2020b, 2021; Zainal et al , 2021). The MHD describes the hydrodynamics of a conducting fluid in the presence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the flow between two parallel plates with the squeezing effect was reported by Salehi et al [32] and Muhammad et al [33]. Apart from that, Waini et al [34] and Khan et al [35] considered the flow towards a shrinking surface. For further reading, the review papers on hybrid nanofluid can be found in Refs.…”
Section: Introductionmentioning
confidence: 95%